Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar PKn di Sekolah Dasar - Desvira, Rezi; Mayarnimar, Mayarnimar; Reinita, Reinita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of the use Jigsaw Cooperative Learning Model on civics learning result of class V elementary school students in cluster III in payakumbuh subdistrict. this research is a quantitative research with the type of experimental research and quas experimental research design. sampling data is done by using cluster random sampling technique. the sample of this study was 32 students. the instruments used in collecting data are objective test with multiple choice forms. that is 1.815 > 1.69726 with α = 0.05. there is an effect of the use of Jigsaw cooperative learning model on Civics III learning outcomes of Class III Elementary School students in Payakumbuh Subdistrict.Keywords  : Jigsaw Cooperative, Student Learning Outcomes, PKn